Developing effective narrative interventions for earthquake survivors - Zang, Yinyin (2013)
Disasters are events that challenge both the social and individual ability to adapt, carrying the risk of adverse mental health outcomes. High prevalence rates of Post Traumatic Stress Disorder (PTSD), anxiety, and depression have been found after disasters among affected adults and children, and PTSD is the most distinct and common disorder. However, the challenge of providing sufficient numbers of mental health professionals is the most critical issue facing health-care systems throughout the world, and especially in developing countries. The 2008 Sichuan earthquake in China had enormous destructive power and affected millions of people. Given the large number of people involved – and the shortage of resources in any major disaster – brief, pragmatic, and easily trainable interventions are needed for both adult and child survivors.